Enhancement of organic thin-film solar cells by incorporating hybrid Au nanospheres and Au nanorods on a metallic grating surface - S. Phetsang (2020)
© 2020 Taylor & Francis Group, LLC. In this study, we demonstrate the fabrication of hybrid plasmonic solar cells using gold nanoparticles (AuNPs). Two types of AuNPs, gold nanospheres (AuNSs) and gold nanorods (AuNRs), were incorporated in a hole transport layer (HTL) (PEDOT:PSS) on a metallic grating electrode. The organic solar cells (OSCs) structure comprised an indium-tin-oxide (ITO)-coated glass substrate/PEDOT:PSS:AuNSs:AuNRs/P3HT:PCBM/Al grating electrode. Adding AuNPs induced localized surface plasmon resonance (LSPR), while grating structured Al at the interface with a photoactive layer excited the propagating surface plasmons. Compared with a flat reference device, the proposed OSCs exhibited improved photovoltaic properties by increasing both the short-circuit current density (JSC) and the power conversion efficiency (PCE) with large enhancements of 16.23% and 14.06%, respectively. The efficiency improvement was attributed to increased broadband absorption and improved electrical properties inside the thin-film devices.